Respuesta :
Answer:
y = -4
x = -2
Step-by-step explanation:
4x - 7y = 20 Eq. 1
x - 3y = 10 Eq. 2
from the Eq. 2:
x = 10 + 3y Eq. 3
substituying Eq. 3 in the Eq. 1
4(10+3y) - 7y = 20
(4*10 + 4*3y) - 7y = 20
(40 + 12y) - 7y = 20
12y - 7y = 20 40
5y = -20
y = 5/-20
y = -4
from the eq. 3:
x = 10 + 3y
x = 10 + 3*-4
x = 10 - 12
x = -2
Check:
from te eq. 1:
4x - 7y = 20
4*-2 - 7*-4 = 20
-8 + 28 = 20
The second equation can also be written as
X= 10+3y
Substitute the x in the first equation with 10+3y
4 ( 10+3y) -7y= 20
40+12y-7y= 20
5y= -20
Y = -4
If y = -4
Then using second equation, plug in y
X - 3 (-4) = 10
X+ 12 = 10
X= -2
X= 10+3y
Substitute the x in the first equation with 10+3y
4 ( 10+3y) -7y= 20
40+12y-7y= 20
5y= -20
Y = -4
If y = -4
Then using second equation, plug in y
X - 3 (-4) = 10
X+ 12 = 10
X= -2